PENGARUH KONSENTRASI KOMBINASI 2,4-D DAN TDZ TERHADAP PERTUMBUHAN TUNAS AKSILER ANGGREK (Dendrobium Red Emperor Prince) - Setiawan, Andri Dias; Mercuriani, Ixora Sartika; Sugiarto, Lili; Ratnawati, Ratnawati; Aloysius, Suyitno (Kingdom: The Journal of Biological Studies, 2024)
Abstrak.Anggrek merupakan tanaman hias yang memiliki nilai ekonomi yang tinggi. Penelitian ini bertujuan untuk mengetahui pengaruh dan konsentrasi optimal zat pengatur tumbuh (ZPT) 2,4-dichlorophenoxy acid (2,4-D) dan  Thidiazuron (TDZ) terhadap pertumbuhan tunas aksiler anggrek Dendrobium Red Emperor Prince. Penelitian ini menggunakan Rancangan Acak Lengkap (RAL) dengan 2 faktor perlakuan yaitu konsentrasi 2,4-D dan TDZ ((0,0), (0,4), (0,5,3), (1,2), (1,5,1) dan (2,0)) dan posisi nodus (atas, tengah dan bawah) sebanyak 6 ulangan. Data dianailisis dengan menggunakan two-way ANOVA dan uji lanjut menggunakan DMRT 5%. Hasil penelitian menunjukan bahwa konsentrasi (0 ppm,4 ppm) mampu menginduksi tunas aksiler dan (1,5 ppm dan 1 ppm) mampu menginduksi akar anggrek Dendrobium Red Emperor Prince lebih baik. Kata kunci: 2,4-D, TDZ, induksi tunas aksiler, Dendrobium Red Emperor PrinceAbstract. Orchids are ornamental plants that have high economic value. This study aims to determine the effect and optimal concentration of plant growth regulators (ZPT) 2,4-dichlorophenoxy acid (2,4-D) and Thidiazuron (TDZ) on the growth of axillary shoots of the Dendrobium Red Emperor Prince orchid. This study used a completely randomized design (CRD) with 2 treatment factors, namely concentrations of 2,4-D and TDZ ((0,0), (0,4), (0,5,3), (1,2), ( 1,5,1) and (2,0)) and node positions (top, middle and bottom) for 6 repetitions. Data were analyzed using two-way ANOVA and follow-up testing using 5% DMRT. The results showed that concentrations (0 ppm.4 ppm) were able to induce axillary shoots and (1.5 ppm and 1 ppm) were able to induce the roots of Dendrobium Red Emperor Prince orchids better.Keywords: 2,4-D, TDZ, axillary shoot induction, Dendrobium Red Emperor PrinceOrchids are ornamental plants that have high economic value. This study aims to determine the effect and optimal concentration of plant growth regulators (ZPT) 2,4-dichlorophenoxy acid (2,4-D) and Thidiazuron (TDZ) on the growth of axillary shoots of the Dendrobium Red Emperor Prince orchid. This study used a completely randomized design (CRD) with 2 treatment factors, namely concentrations of 2,4-D and TDZ ((0,0), (0,4), (0,5,3), (1,2), ( 1,5,1) and (2,0)) and node positions (top, middle and bottom) for 6 repetitions. Data were analyzed using two-way ANOVA and follow-up testing using 5% DMRT. The results showed that concentrations (0 ppm.4 ppm) were able to induce axillary shoots and (1.5 ppm and 1 ppm) were able to induce the roots of Dendrobium Red Emperor Prince orchids better.